Nasopharyngectomy Without Maxillary Swing via a Combined Open Lateral and Endoscopic Approach. (18th July 2022) - Elliott, Zachary; Parsel, Sean; Swendseid, Brian; Xiao, Kevin B.; Sagheer, S. Hamad; Curry, Joseph M.; Rabinowitz, Mindy; Nyquist, Gurston; Rosen, Marc R.; Evans, James; Farrell, Christopher J.; Luginbuhl, Adam J.
Abstract : Nasopharyngeal tumors in the proximity of the internal carotid artery are often difficult to dissect. Here, we describe a combined transcervical and endoscopic endonasal approach that provides improved internal carotid artery protection and confident tumor resection. Laryngoscope, 133:105–108, 2023